CONTRIBUTIONS KH. ABDURRAHMAN NAWI IN DEVELOPING ISLAMIC EDUCATION AT THE AL-AWWABIN ISLAMIC BOARDING SCHOOL, DEPOK - Nurjaya, Nurjaya; Mudzakir , Mudzakir; Muhyi, Abdul (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
The role of a Kyai in developing the progress of Islamic boarding schools is very large, and the role of a Kyai in society is highly expected, starting from solving practical religious problems, providing advice and guidance in life, and developing Islamic education globally. This research aims to analyze the contribution of KH. Abdurrahman Nawi to developing Islamic education at the Al-Awwabin Islamic Boarding School, Depok. The method used in this research is descriptive-qualitative, with data collection techniques in the form of interviews, observation, and documentation. After data collection, the next stage is that the researcher carries out data analysis using three steps: data reduction, data presentation, and drawing conclusions. The research results show that KH. Abdurrahman Nawi contributed to building Islamic educational institutions and became an innovator in providing ideas and suggestions that could be implemented at the Al-Awwabin Islamic boarding school in Depok. In building Islamic educational institutions, he built formal (school) and non-formal (cottage) education. Meanwhile, in providing ideas, he founded many organizations that could develop talents in students, for example, forming a student organization, establishing an Islamic radio channel, honing students' talents, emphasizing understanding of the yellow book, holding muballigh (muhadhoroh) training, making report cards, and boarding school diplomas.